Shifting Reading Habits:: The Role of Digital Resources in Improving Vocabulary for College Students - Nur Hidayah, Siti Aisyah; Mulyadi, Natashya; Fadlillah, Muhammad Fathan; Jaufillaili, Jaufillaili; Mulatsih, Devi; Heryono, Heri (Universitas Jambi, Magister Program of English Education Department, 2025)
Students' reading habits as well as their vocabulary development show gradual changes because of the increased adoption of digital technology. The research investigates digital resource effects on these changes by examining final-year English education students from Universitas Swadaya Gunung Jati Cirebon. A qualitative descriptive research design involved questionnaire and interview data collection methodologies to obtain more accurate and in-depth findings. Students can achieve greater vocabulary development through digital resources, which include mobile apps alongside e-books and online articles, because these resources deliver enhanced reading material accessibility, allowing learners to engage with texts more frequently and in more diverse contexts. The majority of 74% of participants experienced productive vocabulary growth because digital resources help them recognize new words easily and repeatedly in various settings. The survey participants noted that digital resources enabled both better flexibility when reading and increased reading sessions due to the convenience and user-friendliness of such platforms. Therefore, structure common prey-worth resources with curriculum needs to foster improved reading behaviours, which result in higher language advancement for students and support their long-term academic success in English language learning.